ANTITHROMBOTIC THERAPY IN NONVALVULAR ATRIAL FIBRILLATION: PROBLEMS AND PROSPECTS - A. Y. Rychkov (Racionalʹnaâ Farmakoterapiâ v Kardiologii, 2016)
Appropriate use of warfarin is not in routine clinical practice despite convincing data of clinical studies on the possibility of effective reduction in frequency of thromboembolic complications associated with nonvalvular atrial fibrillation, particularly ischemic stroke. Confirmation of the efficacy and implementation of measures related to the effect on blood clotting and providing basically new possibilities to reduce the risk of ischemic events expected in the near future.